Game variables that predict success and performance level in elite men`s volleyball - Drikos, S.; Barzouka, K.; Nikolaidou, M.-E.; Sotiropoulos, K. (International Journal of Performance Analysis in Sport, 2021)
This study examined the Men`s European Volleyball Championship 2019 in which 24 national teams competed. The sample was split into three groups according to its team final ranking. The effectiveness of the main volleyball skills, such as serve, reception, attack after reception, attack after defence and block was calculated. The success rates of each team in side-out and breakpoint complexes were also computed. The reliability of the analysis was examined with Cohen`s Kappa score. Two stepwise discriminant analyses were performed to identify the contribution of each skill`s effectiveness and each complex success rate to winning in a volleyball set and the team`s classification. Cross-validation results showed that the discriminant function correctly classified 91.1% of the teams` performance in win-lose sets and 83.3% of the teams` performance level. The variables which were considered to be central in defining discriminant dimension were break point win(BPwin) = .755 and effectiveness of attack after reception (A1E) = .484 for win-lose sets, and BPwin = .534 and A1E = .454 for performance level, respectively. The results of the study indicate that success in volleyball in a typical set or a tournament can be explained with two performance indicators: the effectiveness of attack after reception and the success rate of breakpoint complex.